2005
DOI: 10.1017/s0958344005000819
|View full text |Cite
|
Sign up to set email alerts
|

Learner interaction using email: the effects of task modification

Abstract: This paper outlines the findings of a research project studying the effects of task modification on learner interaction when using email. Taking as its starting point interactionalist theories of SLA, it argues that if those interactional features characteristic of negotiation of meaning which have been identified as promoting SLA are to be preserved when tasks are transferred from a face-to-face spoken environment to a computer-mediated written asynchronous environment, then modifications to the tasks need to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Smith (2003), on the other hand, found that decision-making tasks supported online negotiation more than jigsaw tasks. Knight (2005), experimenting with face-to-face versus e-mail performance of a hybrid jigsaw and decision-making task, found that, to preserve interactional benefits, faceto-face tasks have to be modified in CMC contexts (in this case, staggering of information). Smith (2005) studied the relationship between negotiation routine complexity, degree of uptake (i.e., learner responses to corrective feedback), and acquisition of vocabulary in a chat environment.…”
Section: Computer-mediated Communicationmentioning
confidence: 99%
“…Smith (2003), on the other hand, found that decision-making tasks supported online negotiation more than jigsaw tasks. Knight (2005), experimenting with face-to-face versus e-mail performance of a hybrid jigsaw and decision-making task, found that, to preserve interactional benefits, faceto-face tasks have to be modified in CMC contexts (in this case, staggering of information). Smith (2005) studied the relationship between negotiation routine complexity, degree of uptake (i.e., learner responses to corrective feedback), and acquisition of vocabulary in a chat environment.…”
Section: Computer-mediated Communicationmentioning
confidence: 99%
“…In recent years, computer-mediated communication (CMC) has been adopted as one of a number of language teaching tools, with email one of the most commonly used forms. A large body of studies on second language (L2) learning via email has established that email interaction enables learners to enhance their language learning experiences (Aitsiselmi, 1999; Florez-Estrada, 1995; Ioannou-Georgiou, 1999; John & Cash, 1995; Knight, 2005; Rooks, 2008; Stockwell, 2003; Stockwell & Stockwell, 2003; Ushioda, 2000; Woodin, 1997). Email has been found to serve as a means for students to access authentic language and learn about culture (Gray & Stockwell, 1998), and Itakura and Nakajima (2001) state that email removes some of the stress associated with communicating in an L2, and provides a record from which to monitor one's own learning processes.…”
Section: Introductionmentioning
confidence: 99%